Navigating self-regulated writing: How EFL Islamic university students use strategies and online resources - Ahmad Ridho Rojabi; Praptika Septi Femilia (JEELS (Journal of English Education and Linguistics Studies), 2025)
Self-Regulated Writing (SRW) is an important strategy as it enables students to initiate, monitor their thinking, and independently evaluate and revise their drafts. This study aims to explore: (1) the Self-Regulated Writing (SRW) strategies employed by EFL students in essay writing, (2) the specific SRW strategies used by advanced students across the PLEE (Planning, Executing, and Evaluating) cycle, and (3) the types of online resources students utilize during the writing. This study used concurrent mixed methods and of the 62 Islamic university students in the essay writing class, 5 were recruited to participate in the semi-structured interviews using purposeful sampling technique. Data from closed-ended questionnaires were analyzed using descriptive statistics, while data from observations and interviews were analyzed thematically. The results demonstrated that in SRW, the social environment dimension is ranked first and the motive dimension is ranked last. During the planning phase, students frequently utilized Google Scholar as an online tool for autonomous writing techniques, while during the execution and evaluation phase, students frequently utilized QuillBot as an online tool for independent writing strategies. Pedagogically, this study contributes to providing valuable insights for educators to design learning experiences that encourages learners to be autonomous in writing.